Malnutrition risk, weight loss, and subsequent survival in patients listed for heart transplantation - Tae Kyung Yoo, MD, MS; Satoshi Miyashita, MD; Ariella Stein, MSCIS-HI; Michael Wu, BS, MPH; Lauren Parsly Read-Button, MPH, RD, LDN; Masashi Kawabori, MD; Greg S. Couper, MD; Edward Saltzman, MD; Amanda R. Vest, MBBS, MPH (JHLT Open)
Background: Higher malnutrition risk is associated with mortality among patients with heart failure and heart transplantation (HT). We investigated which malnutrition risk scores – geriatric nutrition risk index (GNRI), prognostic nutritional index (PNI), or controlling nutritional status (CONUT) – have the strongest mortality association for HT candidates, and whether they are prognostic at the time of HT listing or HT operation. Methods: We reviewed adults listed for primary HT at a single center 1987–March 2022, with survival follow-up to November 2022. We constructed Cox proportional hazards models and restricted cubic spline curves for each risk score at both HT listing and HT operation and inputted HT operation as a time-varying covariate for models commencing at listing. Risk scores were assessed as continuous and binary variables. Weight change between listing and HT was evaluated similarly. Results: The 1,024 patients [76% male; median age 55 (46–61) years; HT operation n = 656] had median follow-up of 4.6 (interquartile range 1.6–8.7) years. As a continuous variable, lower GNRI at HT listing (greater malnutrition risk) was independently associated with higher mortality. As binary variables, higher risk GNRI, PNI or CONUT scores at listing were all associated with higher mortality. Conversely, risk scores at time of HT operation were not associated with subsequent mortality. There was a non-significant trend towards higher mortality with greater weight loss between listing and HT operation. Conclusion: Malnutrition risk scores showed prognostic utility only at time of HT listing. As a continuous variable, GNRI at HT listing was independently associated with subsequent mortality.